A subset of functional adaptation mutations alter propensity for α-helical conformation in the intrinsically disordered glucocorticoid receptor tau1core activation domain - Salamanova, Evdokiya; Costeira-Paulo, Joana; Han, Kyou-Hoon; Kim, Do-Hyoung; Nilsson, Lennart; Wright, Anthony P.H. (Biochimica et biophysica acta, 2018)
Adaptive mutations that alter protein functionality are enriched within intrinsically disordered protein regions (IDRs), thus conformational flexibility correlates with evolvability. Pre-structured motifs (PreSMos) with transient propensity for secondary structure conformation are believed to be important for IDR function. The glucocorticoid receptor tau1core transcriptional activation domain (GR tau1core) domain contains three α-helical PreSMos in physiological buffer conditions. Sixty change-of-function mutants affecting the intrinsically disordered 58-residue GR tau1core were studied using disorder prediction and molecular dynamics simulations. Change-of-function mutations were partitioned into seven clusters based on their effect on IDR predictions and gene activation activity. Some mutations selected from clusters characterized by mutations altering the IDR prediction score, altered the apparent stability of the α-helical form of one of the PreSMos in molecular dynamics simulations, suggesting PreSMo stabilization or destabilization as strategies for functional adaptation. Indeed all tested gain-of-function mutations affecting this PreSMo were associated with increased stability of the α-helical PreSMo conformation, suggesting that PreSMo stabilization may be the main mechanism by which adaptive mutations can increase the activity of this IDR type. Some mutations did not appear to affect PreSMo stability. Changes in PreSMo stability account for the effects of a subset of change-of-function mutants affecting the GR tau1core IDR. Long IDRs occur in about 50% of human proteins. They are poorly characterized despite much recent attention. Our results suggest the importance of a subtle balance between PreSMo stability and IDR activity, which may provide a novel target for future pharmaceutical intervention. •The disordered GRtau1core activation domain contains pre-structured α-helices.•Effects on activity and predicted disorder allow clustering of a set of 60 mutants.•Several clusters are characterized by mutants that affect pre-structured region helicity.•α-Helicity changes of pre-structured regions are an important strategy for adaptation.•Other strategies must account for adaptation in other mutant clusters.